Intergovernmental Harmony: An Imperative for Navigating Covid-19 Pandemic in Nigeria - Agbude, Godwyns Ade’; Afolabi, Temitope (African Journal of Stability and Development (AJSD), 2022)
The reality in the world today has to accommodate the distortions and unprecedented global challenges necessitated by the coronavirus disease which has affected all aspects of human endeavours, thus demanding swift response from the government to chart the course through the pandemic into progress and normalcy as the pandemic has greatly affected all sphere ranging from economic, social, health, educational, to religious aspect of life. An understanding of the crucial role of government in mobilising necessary stakeholders across relevant sectors and levels of government has made harmonious intergovernmental relations paramount in navigating the coronavirus pandemic in Nigeria because all actors must be deliberately engaged in a coordinated manner while leveraging a result-oriented approach to achieve the desired outcome. The methodology used for this research work is qualitative in nature with reliance on secondary data. Systems theory is the adopted theoretical base of analysis, thus, informing the stance of this discourse that intergovernmental relations is key in effectively navigating the pandemic in Nigeria. The study identified that the usual acrimonious interplay between all levels of government in Nigeria will be antithetical to the post-covid-19 developmental effort of the Nigerian State, hence, there is the need for synergy, common alliance, coordination, and unity of purpose between and among all levels of government targeted at making her developmental efforts during and after the pandemic plausible. This study recommends a robust intergovernmental management system that will help coordinate the interactions and relationships between the various governmental levels and actors as this will catalyse sustainable progress in battling the pandemic.